(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study investigates antimicrobial and anti-oxidant potential of different solvent extracted samples from Periploca hydaspidis through disc diffusion assay. The data revealed that all the extracts reduced the growth of the tested microbes using three different concentrations. Pseudomonas aeruginosa and E. coli were sensitive to crude extracts and all fractions measuring varying degree of growth inhibition. Similarly, the growth of Citrobacter freundii was not inhibited by crude methanolic extracts, n-hexane, ethyl acetate and aqueous extracted samples. Maximum growth inhibition was measured against Klebsiella pneumoniae exposed to aqueous fraction followed by n-hexane fraction. Our results also suggested that among various fungi, Candida albicans was sensitive to crude methanolic extracts, n-hexane and aqueous fractions compared with other fractions. The rest of the fungi under test were resistant to crude and all fractions showing no zone of inhibition. All the extracted samples of the stems and roots showed antioxidant activity, however, crude methanolic extract of stem tissues exhibited better antioxidant activity than the other extracts.